The 4 Cs Strategy for disseminating innovations in university teaching: Classroom, Corridors, Campus, Community - Gribble, Lynn; Beckmann, Elizabeth (Journal of University Teaching and Learning Practice, 2023)
University educators are encouraged to be innovative in their teaching practice, and are often recognised and rewarded for these innovations. However, the effective dissemination and consequent adoption of such innovations is still relatively ineffective, despite the development of diverse dissemination frameworks and strategies. The literature suggests the uptake of innovations is constrained especially by ‘people factors’ related to change, transition and perceived risk, which limits the effectiveness of top-down dissemination. Through a reflective methodology guided by an appreciative inquiry stance and the Discover, Dream, Design, Destiny model, the authors explored dissemination of university teaching practices. Through the Discovery phase, the authors reviewed the literature on innovation and dissemination in the context of reflective inquiry into their own experiences as innovative educators. In the Dream and Design phases, the authors used this new understanding to develop an educator-centred approach strategy for sharing innovations in ways that capitalise on people factors and the principles of persuasive influence towards effective change. The 4Cs Dissemination Strategy systematically connects innovators to their students, colleagues, institutions, and broader networks. After building a scholarly evidence base of the impact of teaching innovations in the Classroom, the focus shifts to person-centred interaction with colleagues in Corridors, across the Campus and into the Community. The Destiny phase is in progress: as a structured professional learning framework supporting innovators to become the advocates for their own innovations in practical ways, the 4Cs Dissemination Strategy has the potential to facilitate the sharing of innovative practice and enhance innovation leadership.